2019
DOI: 10.1111/psyp.13495
|View full text |Cite
|
Sign up to set email alerts
|

The neural substrates responsible for how trait anxiety affects delay discounting: Right hippocampal and cerebellar connectivity with bistable right inferior parietal lobule

Abstract: Delay discounting, an indicator of impulsivity, refers to the extent of devaluing future rewards. Studies have found that individuals with trait anxiety generally depreciate the later larger rewards, showing steeper delay discounting rates. However, little is known about the neural substrates responsible for how trait anxiety affects individuals' delay discounting. To address this question, we employed the voxel‐based morphometry (VBM) and resting‐state functional connectivity (RSFC) methods to explore the neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 84 publications
(136 reference statements)
4
17
0
Order By: Relevance
“…T-AI is widely used and suitable for calculating individual's level of trait anxiety. It has been shown to be reliable and valid to use on a Chinese population with a Cronbach's alpha of 0.875 in previous research (Zhang et al, 2019) and 0.855 in the present study. The higher the total score the more likely it is that the subject is prone to anxiety.…”
Section: Trait Anxietysupporting
confidence: 59%
See 4 more Smart Citations
“…T-AI is widely used and suitable for calculating individual's level of trait anxiety. It has been shown to be reliable and valid to use on a Chinese population with a Cronbach's alpha of 0.875 in previous research (Zhang et al, 2019) and 0.855 in the present study. The higher the total score the more likely it is that the subject is prone to anxiety.…”
Section: Trait Anxietysupporting
confidence: 59%
“…The hippocampus has also been related to functions involved in episodic prospective memory (Race, Keane, & Verfaellie, 2013;Schacter, Addis, & Buckner, 2007) for making decisions about future potential outcomes. Those with high trait anxiety may depreciate the future outcomes and be susceptible to negatively anticipating future possibilities (Miloyan, Bulley, & Suddendorf, 2016;Zhang, Chen, Liu, & Feng, 2019). Consistent with this role in episodic prospective memory, Zhang et al (2019) found hippocampal anatomical differences related to trait anxiety and the effects of trait anxiety on intertemporal choice (deciding whether to take a smaller earlier option or waiting for a larger later reward).…”
Section: Role Of the Hippocampus And Episodic Future Thinkingmentioning
confidence: 72%
See 3 more Smart Citations